1974
DOI: 10.1021/es60089a003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of nitric oxide in presence of nitrogen dioxide at atmospheric concentrations

Abstract: Chromium trioxide (CrOg) was tested as a replacement for the potassium permanganate-sulfuric acid solutions designed to oxidize NO for conversion and detection as NO2. The CrOg oxidizer was prepared by soaking firebrick in a 17% solution of pure CrOg, draining, and drying at 105°C. The final loading was about 10% by weight. Since the optimal relative humidity (R.H.) working range of the CrOg oxidizer without sulfuric acid is higher (35-90% R.H.) than the material mixed with sulfuric acid, a humidifier with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 4 publications
0
46
1
Order By: Relevance
“…It was found that the O3 removal was essentially 100% (as checked with a Dasibi Model 1003-AIH ozone detector) while the NO, was passed with only a 5% loss and no change in NO/NOZ ratio. The conversion of NO to NOz was accomplished by inserting into the gas stream a trap, T2, filled with 10% by weight Cr03 on 6-12 mesh silica gel as described by Levaggi et al (25). The trap is an aluminum cylinder 25 cm long and 3.5 cm in diameter with gl!ass wool plugs at both ends to confine the oxidizer.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…It was found that the O3 removal was essentially 100% (as checked with a Dasibi Model 1003-AIH ozone detector) while the NO, was passed with only a 5% loss and no change in NO/NOZ ratio. The conversion of NO to NOz was accomplished by inserting into the gas stream a trap, T2, filled with 10% by weight Cr03 on 6-12 mesh silica gel as described by Levaggi et al (25). The trap is an aluminum cylinder 25 cm long and 3.5 cm in diameter with gl!ass wool plugs at both ends to confine the oxidizer.…”
Section: Acknowledgmentmentioning
confidence: 99%
“…hydroxy-substituted aromatics (Alfassi et al, 1986), aromatic amines (Saltzman, 1954) or alcohol amines (Levaggi et al, 1974). It has also been well established that the photooxidation of aromatic compounds leads to a number of phenols and cresols (Pan et al, 1993) which may further undergo reaction with OH partially leading to several dihydroxy-substituted derivatives (Olariu et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase NO x (NO+NO 2 ), NO 2 , and SO 2 were collected by passing ambient air at a flow rate of about 1 Lmin −1 through the glass impingers placed in sequence containing sodium arsenite (0.008 M), sodium hydroxide (0.1 M) solution (Jacob and Hocheisser 1958), and potassium tetra-chloromercurate solution (0.04 M; West and Gaeke 1956), respectively, and determined by the colorimetric method by an UV-visible spectrophotometer. Further, for NO 2 sampling, ambient air was passed via chromic acid (CrO 3 ) trap to oxidize ambient NO into NO 2 (Levaggi et al 1974). NO is calculated as a difference between NO x and NO 2 .…”
Section: Sampling Sitesmentioning
confidence: 99%